The MAPS triangle. Crossing individual and organizational trajectories within a Portuguese speaking community in Massachusetts - Cordeiro, Graça Índias; Ferro, L. (Neither Here nor There Yest Both: International Conference on the Luso-American Experience, 2013)
The Massachusetts Alliance of Portuguese Speakers (MAPS) is a very important organization in the State of Massachusetts, developing an essential work with the ‘Portuguese speaking community’ (including Portuguese, Brazilian and Cape-Verdean immigrants) in diverse levels (social, economic, political, etc.). Starting from some biographic trajectories of people of different generations very involved with MAPS, we will try to draw the relationship between immigrant’s situation and the achievements of this organization. We will draw the mentioned relation by crossing the individual trajectories with the history of MAPS. The background of this exercise is the concerning with the understanding of the role of MAPS in local communities in the Boston area, where MAPS acts more directly. Our paper is a result of an ethnographic fieldwork supported by FLAD, during 2011.